Hubungan Dukungan Keluarga dengan Tingkat Kecemasan Lansia Yang Mengalami Diabetes Melitus Tipe 2 di Puskesmas Cigugur Tengah 2024: Diabetes Melitus Tipe 2, Dukungan Keluarga, Tingkat Kecemasan, Lansia - Suhandi, Nadiya Aurelia; Noch Bolla, Ibrahim; Imelisa, Rahmi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background: Type 2 Diabetes Mellitus is an annual disease that occurs due to damage to the pancreatic system to produce insulin, therefore people who have diabetes mellitus tend to experience anxiety due to the disease, therefore family support will greatly affect the level of anxiety experienced by people with diabetes mellitus. Objective: to determine the relationship between family support and the anxiety level of the elderly who experience type 2 diabetes mellitus at the Central Cigugur Health Center. Method: analytic survey with a cross sectional approach. The number of samples in this study were 59 patients with type 2 diabetes mellitus with elderly age (>60 years) at the Central Cigugur Health Center. Samples were selected using convenience sampling technique. The research instruments used were the Hensarling Diabetes Family Support Scale (HDFSS) questionnaire and the Geatric Anxiety Inventory (GAI). Data analysis in this study using univariate and bivariate analysis with the chi square test. Result: 69.5% of respondents who received low family support. Meanwhile there were 45.8% of respondents who had mild anxiety, as a result of lack of family support the patient experienced anxiety. It is proven that there is a significant relationship between family support and the anxiety level of the elderly who experience type 2 diabetes mellitus, with a p value of 0.001 < α (0.05). Conclusion: There is a significant relationship between family support and the level of anxiety in elderly people who suffer from type 2 diabetes mellitus Keywords: : Anxiety, type 2 diabetes mellitus, elderly, family support